Spike wave characteristics and temporal spike evolution on serial EEG in childhood epilepsy with centrotemporal spikes. (April 2021) - Tekgul, Hasan; Kanmaz, Seda; Serin, H. Mine; Yılmaz, Sanem
Highlights: 4 The spike characteristics of EEG are valuable in CECTS. 4 The spike clearance velocity on serial EEGs is related to the rate of seizure recurrence. 4 Spike clearance velocity might be a valuable EEG marker to guide anti-seizure medication. Abstract: Purpose: To assess the spike characteristics and temporal spike evolution on serial EEG of children with childhood epilepsy with centrotemporal spikes (CECTS) treated with anti-seizure medication. Methods: The study cohort consisted of 127 children with CECTS divided into three groups based on anti-seizure medication responsiveness: group I: seizure-free with monotherapy (n: 61, 48%), group II: seizure-controlled with monotherapy (n: 52, 41%) and group III: seizure-controlled with dual therapy (n: 14, 11%). The clinical profiles and sequential four-year follow-up visual EEG recordings of the children were evaluated. Each EEG was reanalyzed with three spike characteristics on the epochs: (1) spike-wave rate, (2) spike topography, and (3) spike localization. We calculated the spike clearance velocity, which is defined as a decrease in the spike-wave rate over time in four-year sequential follow-up EEGs. Results: There was no statistical significance across the study groups with respect to initial EEG spike characteristics (spike-wave rate, spike localization, and spike topography). Seizure recurrence occurred in 15 patients (12.8%) who discontinued anti-seizure medication. There was no statistically significant difference between the spike characteristics on EEG just before the discontinuation of anti-seizure medication and seizure recurrence. However, the spike clearance velocity was significantly slower in group III than in group I in four-year sequential follow-up EEGs ( p  = 0.002). A statistically significant decrease in the mean spike-wave rate was observed in group I in the first year of anti-seizure medication ( p <0.001). The spike clearance velocity was also more prominent during the second year of treatment in group II and the third year of treatment in group III. However, the spike clearance velocity was not different across the anti-seizure medication groups (oxcarbazepine, valproic acid, and levetiracetam). Conclusion: Spike clearance velocity might be a valuable EEG marker to guide anti-seizure medication in children with CECTS.